2012
DOI: 10.1097/pgp.0b013e3182469583
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Adiponectin Receptors are Decreased in Human Endometrial Adenocarcinoma Tissues

Abstract: Adiponectin is a cytokine secreted by adipocytes, whose plasma levels are decreased in obesity. Adiponectin has insulin-sensitizing, antiatherogenic, and antidiabetogenic effects. It has been shown that adiponectin may also exert antineoplastic activity through suppression of tumor proliferation and neoangiogenesis and through induction of apoptosis. Recently, low adiponectin serum concentration has been found in obesity-related malignancies, including endometrial cancer. In addition, the expression of adipone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
0
25
1
1
Order By: Relevance
“…Decreased adiponectin receptor 1 (AdipoR1)/AdipoR2 expression has also been shown to be closely associated with neoplastic growth of the endometrium. Investigators reported lower levels of AdipoR1 in endometrial adenocarcinoma patients with myometrial invasion or lymph node metastasis (Yamauchi et al 2012). It has been postulated that adiponectin may prevent tumorigenesis by activating AMPK and inhibiting phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR signaling via AdipoR1/2 (Schmandt et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased adiponectin receptor 1 (AdipoR1)/AdipoR2 expression has also been shown to be closely associated with neoplastic growth of the endometrium. Investigators reported lower levels of AdipoR1 in endometrial adenocarcinoma patients with myometrial invasion or lymph node metastasis (Yamauchi et al 2012). It has been postulated that adiponectin may prevent tumorigenesis by activating AMPK and inhibiting phosphatidylinositol 3-kinase (PI3K)/AKT/mTOR signaling via AdipoR1/2 (Schmandt et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Henece, adiponectin receptor expression decrese is a proposed contributor to cancer progression and currently is a proposed target of treatment for endometrioid adenocarcinomas [69]. In one study, KLE and RL95-2 human endometrial cancer cell lines had a decrease in proliferation when incubated with adiponectin [70].…”
Section: Adiponectinmentioning
confidence: 99%
“…Decreased adiponectin receptor expression is associated with a histological higher grade of endometrial cancer [69]. Henece, adiponectin receptor expression decrese is a proposed contributor to cancer progression and currently is a proposed target of treatment for endometrioid adenocarcinomas [69].…”
Section: Adiponectinmentioning
confidence: 99%
“…Here we briefly mention the following supportive observations. First of all, leptin and adiponectin receptor density in EC tumor tissue correlates directly for leptin and inversely for adiponectin receptors, with regional lymph nodes involvement [48,49]. On the other hand, total serum testosterone levels tend to be higher in patients with EC [50] as it occurs in postmenopausal women with developing insulin resistance [51].…”
Section: Discussionmentioning
confidence: 99%